Multibeam laser–plasma interaction at the Gekko XII laser facility in conditions relevant for direct-drive inertial confinement fusion. (20th February 2023) - Cristoforetti, G.; Koester, P.; Atzeni, S.; Batani, D.; Fujioka, S.; Hironaka, Y.; Hüller, S.; Idesaka, T.; Katagiri, K.; Kawasaki, K.; Kodama, R.; Mancelli, D.; et al.
Abstract: Laser–plasma interaction and hot electrons have been characterized in detail in laser irradiation conditions relevant for direct-drive inertial confinement fusion. The experiment was carried out at the Gekko XII laser facility in multibeam planar target geometry at an intensity of approximately $3× {10}^{15}$ W/cm 2 . Experimental data suggest that high-energy electrons, with temperatures of 20–50 keV and conversion efficiencies of $η <1%$, were mainly produced by the damping of electron plasma waves driven by two-plasmon decay (TPD). Stimulated Raman scattering (SRS) is observed in a near-threshold growth regime, producing a reflectivity of approximately $0.01%$, and is well described by an analytical model accounting for the convective growth in independent speckles. The experiment reveals that both TPD and SRS are collectively driven by multiple beams, resulting in a more vigorous growth than that driven by single-beam laser intensity.